(untitled) (University Journal of Zoology, Rajshahi University, 2012)
This paper examines the effect of density and temperature on the functional response of adult female Phytoseiulus persimilis to different life stages of the spider mite, Tetranychus urticae. The functional response was determined using functional response assay technique with plant leaf discs an arena. We conducted a logistic regression of the proportion of prey consumed as a function of initial prey density to identify functional response types, and used nonlinear least-squares regression and the random predator equation to estimate attack rates and handling times. In all the cases number of adult male prey attacked by female predator were greater than adult female prey. P. persimilis consumed more eggs and larvae than other stages of prey. Female predator consumed adult prey at each temperature which generally increased with prey density initially but leveled off at higher prey densities. The highest number of eggs, larvae and nymphs consumed by predator in 24 hours was 16.3 ± 0.42, 9.9 ± 0.59 and 9.5 ± 0.40 respectively whereas the highest number of eggs, larvae and nymphs consumed by a single female in 48 hours was 19.5 ± 1.15, 18.6 ± 0.62 and 13.3 ± 0.65 respectively. Handling time generally decreased with temperature whereas successful attack rate increased with temperature except at 30º C. Judging by a/Th values, P. persimilis was most efficient against T. urticae at 30-35ºC, about half as efficient at 25 ºC and performed poorly at 20º C. Again, from a/Th values, P. persimilis was most efficient against T. urticae in egg stage, about half as efficient at larva and nymph stages and performed poorly at adult stage. Key words: Phytoseiulus persimilis; Tetranychus urticae; functional response; predation; temperature. DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9458 UJZRU 2010; 29(1): 1-8